Hepatoprotective and antioxidant activity of Melaleuca styphelioides on carbon tetrachloride-induced hepatotoxicity in mice. (December 2014) - Al-Sayed, Eman; El-Lakkany, Naglaa M.; Seif el-Din, Sayed H.; Sabra, Abdel-Nasser A.; Hammam, Olfat A.
Abstract Context: Liver disease is a serious problem. Polyphenolic compounds have marked antioxidant effect and can prevent the liver damage caused by free radicals. In vitro studies have revealed the strong antioxidant activity of an ellagitannin-rich plant, namely, Melaleuca styphelioides Sm. (Myrtaceae). Objective: In view of the limited therapeutic options available for the treatment of liver diseases, the hepatoprotective potential of the methanol extract of M. styphelioides leaves (MSE) was investigated against CCl4-induced liver injury in mice. Materials and methods: MSE was administered (500 and 1000 mg/kg/d p.o.) along with CCl4 for 6 weeks. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were determined in the serum. Glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione transferase (GST), and malondialdehyde (MDA) were estimated in the liver homogenate. The bioactive components of MSE were identified by NMR, UV and HRESI-MS/MS data. Results: MSE treatment (500 and 1000 mg/kg/d) markedly inhibited the CCl4-induced increase in the levels of AST (31 and 38%), ALT (29 and 32%), ALP (13 and 19%), and MDA (22 and 37%) at the tested doses, respectively. MSE treatment markedly increased the levels of GSH (29 and 57%) and antioxidant enzymes compared with the CCl4-treated group. MSE was more effective than silymarin in restoring the liver architecture and reducing the fatty changes, central vein congestion, Kupffer cell hyperplasia, inflammatory infiltration, and necrosis induced by CCl4. The LD50 of MSE was more than 5000 mg/kg. Conclusion: MSE confers potent antioxidant and hepatoprotective effects against CCl4-induced toxicity.